1988
DOI: 10.1088/0022-3727/21/6/008
|View full text |Cite
|
Sign up to set email alerts
|

Arc velocity and cathode erosion rate in a magnetically driven arc burning in nitrogen

Abstract: Measurements of the arc velocity and of the erosion rate are reported for a copper cathode. The 100 A arc, burning in nitrogen, is driven by a magnetic field B, varying from 5.1 to 171.0 mT, between concentric copper electrodes having an inter-electrode gap of 4 mm. The arc velocity varied with B0.60 throughout the range investigated. The erosion rates dropped from 9.0 to 1.0 mu g C-1 as the arc velocity was increased from 15 to 135 m s-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
7

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 18 publications
2
39
0
7
Order By: Relevance
“…The optimization of this magnetic field, B ¼ 0.1 T, enables the arc to be kept nearly vertical throughout its movement across the plane electrode (Figure 4(b)). The average velocity of the arc column, at the test gap region, under these conditions is about 24 m/s, which is 2.5 times faster than the case without an added external field, reducing considerably contact erosion and metal vapor generation [18].…”
Section: Arc Kinematics and Structurementioning
confidence: 84%
See 1 more Smart Citation
“…The optimization of this magnetic field, B ¼ 0.1 T, enables the arc to be kept nearly vertical throughout its movement across the plane electrode (Figure 4(b)). The average velocity of the arc column, at the test gap region, under these conditions is about 24 m/s, which is 2.5 times faster than the case without an added external field, reducing considerably contact erosion and metal vapor generation [18].…”
Section: Arc Kinematics and Structurementioning
confidence: 84%
“…During the running phase the arc lengthens due to the anode shape, presenting an angle of 18 with the horizontal axis (see Figure 1). The precise shape of the arc runners was chosen in order to keep the arc as close to the vertical axis of the test gap as possible.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…For the scope of this research, however, tests were performed in ambient air exclusively. The use of transverse magnetic fields to continuously move an electric arc on the electrode surface has been studied regularly in the past [32], often with the goal of reducing localized heating and electrode erosion [33]. It has also been suggested as a method to improve switching performance of disconnectors [34].…”
Section: Fast-acting Disconnector: Resultsmentioning
confidence: 99%
“…The less than linear increase of speed with current can be attributed to the linear increase of Lorentz force with current, which is counteracted by aerodynamic drag growing with the square of the speed. Guile et al [32] give a proportionality of v ∝ I 0.4 , while Szente et al [33] found v ∝ I 0.60 . In the presented data it is also evident that arc speed decreases with opening distance.…”
Section: Arc Rotation In Air: Speed and Voltagementioning
confidence: 95%
See 1 more Smart Citation